ANALYSIS OF COMPENSATION PRACTICES IN HAJJ ARRUM PRODUCTS ACCORDING TO FIQH MUAMALAH : STUDY ON BANDA ACEH SHARIA PAWNSHOP - Fanisa, Yara; Hakim, Ahmad Luqman (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
One of the superior products of Pegadaian Syariah is the Hajj arrum product which provides Hajj assistance funds by pawning gold weighing 3.5 grams or the equivalent of 1.5 gold mayams, and customers have received a loan of IDR 25,000,000 to register for the Hajj portion. Pegadaian Syariah is inseparable from the risk of loss, so compensation (ta'widh) is applied. The determination of ta'widh must be in accordance with the applicable rules in accordance with the Fatwa DSN-MUI and Islamic Law. This type of research uses qualitative research methods and uses a normative-empirical legal approach with data from laws and regulations, fatwas of scholars, and other secondary data. The results showed that the mechanism of compensation practices in the Arrum Haji product at Pegadaian Syariah Darussalam Banda Aceh, this has been determined by the nominal amount of a maximum percentage of 4% which has been made in accordance with the institution's regulatory policies and agreed upon by the customer. However, the amount of compensation is only made by one party and the customer only follows the rules without knowing what form of loss the Sharia Pawnshop will experience if the customer delays in paying the financing installments. So that the implementation of the practice of compensation (ta'widh) is not in accordance with the contents of the MUI DSN Fatwa No. 43 / DSN-MUI / VIII / 2004 concerning compensation (ta'widh) which explains how the practice of compensation (ta'widh) should not include nominal losses, but must be in accordance with the actual losses or real losses incurred by the customer.